2017
DOI: 10.2306/scienceasia1513-1874.2017.43.347
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles and antioxidant properties of dabai oil

Abstract: Supercritical CO 2 (SC-CO 2) was used to extract dabai oil. Total phenolic content, total flavonoid content, DPPH radical scavenging assay, and gas chromatography analysis were performed to determine the antioxidant properties of SC-CO 2-extracted dabai oil and to compare with hexane-extracted dabai oil. The total phenolic content of SC-CO 2-extracted oil was slightly higher than hexane-extracted oil, whereas the total flavonoid content of SC-CO 2extracted dabai oil was four times lower than the hexane-extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Table 1 below compares research done by other authors with the current study. Jelani et al (2017) conducted research involving the extraction of dabai from pulp using hexane solvent and supercritical carbon dioxide fluid extraction (SC-CO2) which exhibited 3% and 0.71% respectively [4]. The author suggested the low antioxidant activity of dabai pulp might be because of weak interactions of the solvent with the antioxidant components in dabai pulp and suggested extraction with ethanol to potentially exhibit more antioxidant activity of dabai pulp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 below compares research done by other authors with the current study. Jelani et al (2017) conducted research involving the extraction of dabai from pulp using hexane solvent and supercritical carbon dioxide fluid extraction (SC-CO2) which exhibited 3% and 0.71% respectively [4]. The author suggested the low antioxidant activity of dabai pulp might be because of weak interactions of the solvent with the antioxidant components in dabai pulp and suggested extraction with ethanol to potentially exhibit more antioxidant activity of dabai pulp.…”
Section: Resultsmentioning
confidence: 99%
“…Locals indulge the fruit by softening it in warm water then with sugar or salt and pickling it in soy sauce. Along the years, researchers have investigated the antioxidant capacity for different parts of dabai, including the skin, seed and pulp [4,5]. It was revealed that the skin of dabai possesses the highest antioxidant capacity among all the other parts [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously optimized the SCO 2 extraction conditions and established a laboratory protocol for the CO fat extraction (Jelani et al, 2017). However, the extraction of CO fat was done based on the semi-pilot scale, and the optimized extraction condition was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The fatty acid profile of dabai pulp oil is similar to that of palm oil. As a result, dabai pulp oil can most likely be used as a vegetable oil substitute [ 62 ]. Growing recognition of the value of vegetable oils and their health benefits in achieving sustainable development goals has sparked economic interest in their ability to be transformed into agricultural and industrial products.…”
Section: Potential Of Food Products and Essential Oil Processing Of D...mentioning
confidence: 99%